Sport psychiatry – a new frontier in a challenging world - Glick, I. D.; Morse, E.; Reardon, C. L.; Newmark, T. (Die Psychiatrie, 2010)
This paper provides an overview of the field of sport psychiatry, including what a psychiatrist does, data on psychiatric issues related to athletes, evolution of the field, how to break into the field, and needs and challenges. Further controlled research is greatly needed, but 2010 may be the moment in time that the field blossoms and grows into maturity.
Keywords: Sports psychiatry; psychiatric disorders; child/adolescent psychiatric issues